Mestres que criam: a produção do conhecimento no Mestrado Profissional em Artes no Estado do Pará - MENEZES, Joaquim Augusto Souza de (Universidade Federal do Pará, 2020)
The thesis analyzes, through subjectivity and in a narrative way, the production of knowledge in the Professional Master in Arts, aiming at the development of a theoretical framework that supports the strengthening of Educational Policy for the improvement of Basic Education. Therefore, it was necessary to study and reflect, respectively, on the twenty-five textual productions and essay products; in addition to identifying a minimum set of guidelines. The research was of a qualitative approach in the analysis of the twenty-five productions generated by the master's students of the 2014 and 2016 classes. The theoretical references are based on the Systematization of Brazilian Education. The results of the studies emphasize that the State of Pará, through Public Universities, can and should strengthen Postgraduate Programs focused on Basic Education. And it recommends the need for future studies, such as: identifying which professional training courses are necessary to promote the development of the municipalities and mesoregions studied, both at undergraduate and graduate levels; analyze the impacts arising from the participation of teachers in the Professional Master's Course in Arts; as well as to evaluate the capacity of the Public Universities of the State of Pará to install the Professional Master's Course in Arts, and other Professional Master's Courses in the various mesoregions of the State of Pará.